The role of attentional deployment during distancing in adolescents with major depression. (March 2020) - Greimel, E.; Piechaczek, C.; Schulte-Rüther, M.; Feldmann, L.; Schulte-Körne, G.
Abstract: Individuals with major depression (MD) show deficits in cognitive reappraisal. It is yet unexplored how the act of directing visual attention away from/towards emotional aspects impacts on cognitive reappraisal in MD. Thus, we examined the role of attentional deployment during cognitive reappraisal (specifially during distancing) in adolescent MD. 36 MD adolescents and 37 healthy controls (12–18 years) performed a cognitive reappraisal task during which they a) down-regulated self-reported negative affective responses to negative pictures via distancing, or b) simply attended to the pictures. During the task, attentional focus was systematically varied by directing participants' gaze to emotional vs. non-emotional picture aspects. The validity of this experimental manipulation was checked by continuous eye-tracking during the task. Across groups and gaze focus conditions, distancing diminished negative affective responses to the pictures. Regulation success significantly differed between groups dependent on gaze focus: MD adolescents showed relatively less regulation success than controls in the emotional gaze focus condition, while the reverse was true for the non-emotional gaze focus condition. The results suggest that in MD adolescents, an emotional context might interfere with emotion regulatory aims. The findings can provide an important starting point for the development of innovative training regimes that target deficient reappraisal processes in adolescents suffering from MD. Highlights: We tested the role of attentional deployment during distancing in youth MD. Depressed and healthy adolescents completed a distancing task. During distancing, gaze focus was directed to emotional or non-emotional aspects. Regulation success differed between groups dependent on gaze focus. Data suggests that an emotional context interferes with regulatory aims in youth MD.